Etos Kerja, Motivasi, dan Sikap Inovatif Terhadap Produktivitas Petani - Iskandar, Otto (UI Scholars Hub, 2002)
The objective of the study is to analyze rela tionships between work ethos, achieve-ment of motivation and attitude of innovation and productivity of the farmer individually as well as simultaneusly. The study was carried out at Kuningan West Java (1999) with 60 respon dents selected randomly. The study reveald that there is positive correlation between : (1) Work ethos and pro duc tivity of the farmers (2) achievement of motivation and pro ductivity of the farmers (3) attitude of innovative and productivity of the farmers. Together, there is positive relationship between work ethos, achievement of motivation and attitude of innovative with productivity of the farmers. The research implies that work ethos, achievement of motivation and attitude of innovative useful to predict the productivity of the farmers.